Decolorization of textile wastewater by electrooxidation process using different anode materials: Statistical optimization - Turan, Nouha Bakaraki; Erkan, Hanife Sari; Ilhan, Fatih; Engin, Guleda Onkal (WILEY, 2022)
The presence of reactive dyes in textile wastewater is a serious environmental concern due to their associated mutagenic and carcinogenic effects. The present study aims to analyze the effect of different anodic materials on the decolorization of a real textile wastewater effluent. For this purpose, four different anodic materials-TiO2-coated platine, TiO2-coated ruthenium dioxide (RuO2) (viz., RuO2), titanium dioxide (TiO2), and graphite-were connected, respectively, to titanium dioxide (TiO2) used as a cathode electrode. Color and cost optimization studies were performed using the response surface methodology and the Box-Behnken experimental design (BBD). According to ANOVA results, the R2 values for Pt/TiO2, RuO2/TiO2, TiO2/TiO2, and graphite/TiO2 electrode pairs were found to be 97.4%, 93.8%, 92.44%, and 92.2%, respectively, indicating a good compatibility as it is close to one. The results show that color removal efficiencies at the optimal conditions were 86.3%, 90.8%, 91.5%, and 93.6% for Pt/TiO2, graphite/TiO2, TiO2/TiO2, and RuO2/TiO2, respectively. Furthermore, energy consumption cost at the optimum conditions was also evaluated, and the results were as follows: Pt/TiO2 (0.95 euro/m3), graphite/TiO2 (0.74 euro/m3), TiO2/TiO2 (0.31 euro/m3), and RuO2/TiO2 (0.26 euro/m3). Consequently, this research paper shows that all of the tested anodic materials give satisfactory color removal efficiencies higher than 86%. When energy consumption and color removal are considered together, the use of TiO2/TiO2 and RuO2/TiO2 pairs would be preferred. Practitioner Points Anodic contribution was investigated for decolorization of textile wastewater by electrooxidation process. Graphite, TiO2-coated Pt, TiO2-coated RuO2, and TiO2 were used as anode materials. Highest color removal with lowest energy consumption was achieved with TiO2-coated RuO2 anode material (93.6%).
Keywords: decolorization; electrooxidation; RuO2 electrode; textile wastewater; TiO2 electrode; ADVANCED OXIDATION PROCESSES; ELECTRO-FENTON PROCESS; ELECTROCHEMICAL OXIDATION; ELECTROCOAGULATION PROCESS; ORGANIC POLLUTANTS; TREATMENT PLANTS; AQUEOUS-SOLUTION; METHYLENE-BLUE; DEGRADATION; DYES; Engineering; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources